Circulating MicroRNA-505 May Serve as a Prognostic Biomarker for Hypertension-Associated Endothelial Dysfunction and Inflammation - Yang, Qinbo; Wang, Peiwei; Cai, Yiqing; Cui, Yimeng; Cui, Jingang; Du, Xiaoye; Chen, Yu; Zhang, Teng (Frontiers in Cardiovascular Medicine, 2022)
Our previous study has reported that the plasma microRNA-505 (miR-505) is elevated in hypertensive patients. However, the pathophysiological significance of miR-505 in hypertension remains to be elucidated. Hypertension is not only a vascular disorder, but also an inflammatory condition. The current study therefore aims to further investigate the pathophysiological implications of miR-505 in hypertension-associated vascular and inflammatory changes. In vivo experiments reveal that the plasma level of miR-505 is elevated in spontaneously hypertensive rats and angiotensin II-infused mice. In addition, miR-505 agomir treatment results in elevated blood pressure, endothelial dysfunction, increased vascular expression of inflammatory genes and renal inflammatory injuries as well as pre-activation of PBMCs in mice. In vitro experiments further demonstrate that miR-505 agomir increases the expression of IL1B and TNFA, whereas miR-505 antagomir attenuates TNF-α-induced upregulation of IL1B and TNFA in endothelial cells, HUVECs. In addition, miR-505 modulates the levels of endothelial activation markers VCAM1 and E-selectin in HUVECs as well as the adhesion of THP-1 monocytes to HUVECs. Lastly, the plasma level of miR-505 is positively correlated with systolic blood pressure and the level of C-reactive protein in human subjects. Our work links for the first time miR-505 to endothelial dysfunction and inflammation under hypertensive conditions, supporting the translational value of miR-505 in prognosticating hypertension-associated endothelial impairment and inflammatory injuries in target organs such as the vessels and kidneys.